Investigação da influência da estrutura cristalina no efeito exchange bias espontâneo da série La1,5(Sr0,5-xBax)CoMnO6 - Belluzi, Marlon Boldrin (2021)
The exchange bias (EB) effect is of great academic interest due to its potential applications in spintronics. Recently there were discovered some material exhibiting the EB effect spontaneously, i.e., even after being cooled in the absence of an external magnetic field. The main focus of this work is to investigate the influence of crystalline and electronic structures on the spontaneous EB effect. Therefore, here we describe the synthesis and structural, electronic and magnetic characterizations of polycrystalline samples of the La1.5(Sr0.5-xBax)CoMnO6 series. The main objective was to investigate the evolution of the magnetization of the system when Sr is gradually substituted by Ba. Polycrystalline samples were synthesized by conventional solid state reaction, and their structural properties were characterized by powder X-ray diffraction and the Rietveld Refinement. The magnetic properties were investigated by means of magnetization as a function of temperature [M(T)] and magnetization as a function of magnetic field [M(H)] measurements. The compounds were formed in a single phase, in the rhombohedral space group 3̅c. In addition, it was observed that the lattice parameters increase as the Ba concentration increases. The M(T) measurements indicate that all compounds have ferromagnetic (FM) and antiferromagnetic (AFM) ordering, where an increase in the proportion of the AFM phase was observed as the Ba concentration increases. Also, a trend of change is observed in the average spin state of the Co3+ ions, which varies from the low spin (LS) configuration to the high spin (HS) configuration as the Ba concentration increases. The M(H) measurements performed after cooling the samples in zero field showed a robust spontaneous EB effect, with the concentration x = 0.25 having the greatest effect ever observed. M(H) measurements taken after cooling the materials in the presence of an external field showed a qualitative behavior similar to those taken after cooling in zero field. The variations in the exchange bias effect observed throughout the series can be explained by the variations in the AFM phase and in the spin state of Co3+.